Women’s work empowerment through “reupcycle” initiatives for women-at-home - Rokis, Rohaiza (IIUM Press, International Islamic University Malaysia, 2018)
Recyclable issues do not receive sufficient attention, which thus see low awareness among Malaysians. This paper1 proposes women’s active participation in re-upcycling habits to maintain the ecologically challenging world today. Empowering women-at-home in this way enable them to sustain their own social and ecological well-being. Women can be active participants in community development activities. Even though they may be disinterested to work outside home, their involvement in their community should be encouraged. Embeddedness theory (ET) advocates empowerment of women through re-upcycling actions are to be initiated from home. With the support from community, in turn, these actions can be an economic resources for their households. Malaysian women are most affected by employment opportunities, supports and reassurances from various sectors, such as the government, nongovernmental organisations (NGOs) and most importantly, the men in their lives. Depriving them from this socio-economic foundation will further impact the unemployment rate for Malaysia. On the other hand, if strategic planning is implemented by utilising the abundance number of unemployed women-at-home, the socio-economic conditions of the nation can also be improved. Indeed, this paper motivates discussions on the employment policy whereby re-upcycling activities may pave ways for women-at-home to get involved in employment, without leaving their homes.